Dover Chemical's Doverphos LGP-11 receives expanded FDA clearance for food contact. Issue 5 (May 2017) - Unknown
Abstract : Ohio-based Dover Chemical Corp has received expanded-use clearance from the US Food and Drug Administration (FDA) for liquid antioxidant Doverphos ® LGP-11 ® as a thermal stabilizer in polypropylene (PP) and high impact polystyrene (HIPS) used as components of finished food packaging and repeated-use articles in contact with all types of food. The approval covers Conditions of Use A (high-heat sterilization) through H (frozen storage), as defined by the Federal Food, Drug, and Cosmetic Act, at loading levels of the antioxidant in the polymer of up to 2000 ppm.